Immunohistochemical expression of bcl-2; an apoptosis regulatory protein in squamous cell carcinoma of oropharynx: A diagnostic cross-sectional study. (July 2021) - Bhutani, Namita; Poswal, Pooja; Moga, Shilpi; Arora, Sunil
Abstract: Background: The Oropharyngeal squamous cell carcinoma is the second most common head and neck malignancy. Bcl-2 expression alterations have been reported invariably in different cancers. It plays a part in carcinogenesis by inhibiting programmed cell death and thus increasing cell survival. Materials and methods: The present study was conducted in Department of Pathology, S.G.T. Medical College and University, Gurugram over a period of one year (2019–20) on biopsy proven cases of squmaous cell carcinoma of oropharynx. Grading of the tumor was done using Anneroth's multifactorial grading system. The Bcl-2 scoring was done. Results: In the present study, a total of 75 cases of oropharyngeal SCC constituted the study group, with the mean age at presentation of 56.63 years. The correlation between Anneroth's grading system and WHO grade was found to be statistically significant, while correlation between WHO grade with lymph node status was found to be statistically non significant. Conclusion: There was significant correlation between Anneroth's grading system and WHO grading system in SCC of oropharynx and it was found to be more relevant in predicting the stage of tumor. Bcl-2 expression did not correlate with the grading of tumor. Highlights: The burden of head and neck cancer in India can be regarded as 'tip of iceberg' situation'. Bcl-2 plays a part in carcinogenesis by inhibiting programmed cell death and thus increasing cell survival. The expression of bcl-2 rises with increasing grade of tumor. Bcl-2 status is closely associated to the success of chemoradiation treatment of oropharyngeal SCC.